The Foresight of Dark Knowing Chŏng Kam nok and Insurrectionary Prognostication in Pre-Modern Korea - Jorgensen, John (Korean Classics Library: Philosophy and Religion, 2018)
Korea has long had an underground insurrectionary literature. The best-known example of the genre is the Chŏng Kam nok, a collection of premodern texts predicting the overthrow of the Yi Dynasty (1392–1910) that in recent times has been invoked by a wide range of groups to support various causes and agendas: from leaders of Korea’s new religious movements formed during and after the Japanese occupation to spin doctors in the South Korean elections of the 1990s to proponents of an aborted attempt to move the capital from Seoul in the early 2000s.Written to inspire uprisings and foment dissatisfaction, the Chŏng Kam nok texts are anonymous and undated. (Most were probably written between the seventeenth and late nineteenth centuries.) In his expansive introduction to this first English translation, John Jorgensen notes that the work employs forms or codes of political prediction (Ch. tuch’en; Kor.